Towards a green internal electricity market: The self-regulation of European Transmission System Operators for Electricity within EU multilevel governance - Anna Brüning (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2014)
Due to the 3rd Energy Package of 2009 the regulation of European electricity transmission did change considerably. Before, cross-border electricity issues have been regulated by voluntary contractual agreements between Transmission System Operators. Now, the new-founded Agency for the Cooperation of Energy Regulators (ACER) and the European Network of Transmission System Operators for Electricity (ENTSO-E) are guiding this process together with the European Commission. Currently, these organizations are developing network codes to be implemented as binding EU electricity transmission regulation within the next years. This paper analyzes, if this new regulation process does promote the creation of an internal electricity market as well as a better integration of intermittent renewable ('green') energies due to the multilevel governance approach.
Keywords: L43; L59; L94; 330; EU Energy Policy; Transmission Grids; Renewable Energies; Regulation Theory; Multi-level Governance Theory